The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/dad.0b013e31812f66c4
|View full text |Cite
|
Sign up to set email alerts
|

Polarizable Material as a Clue

Abstract: A healthy 22-year-old college student presented with 2 itchy, painful scalp nodules associated with intermittent lancinating pain. Lesions appeared after an alleged mosquito bite during his vacation in Belize. He initially presented to an emergency department and was diagnosed with cellulitis unresponsive to treatment with antibiotics and antifungal medication. FIGURE 1. Physical examination of the scalp reveals 2 warbles--boggy plaques with a central punctum and intermittently draining serosanguineous fluid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…The only birefringent area was a part of the mouth apparatus, which exhibited a yellowish birefringence, as well as its intestinal contents. These findings contrast with claims in the literature regarding the role of polarization as an indicator in the diagnosis of myiasis . In our opinion, the birefringence of amorphous pigmented fragments points to vegetable pericarp rather than to animal parts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The only birefringent area was a part of the mouth apparatus, which exhibited a yellowish birefringence, as well as its intestinal contents. These findings contrast with claims in the literature regarding the role of polarization as an indicator in the diagnosis of myiasis . In our opinion, the birefringence of amorphous pigmented fragments points to vegetable pericarp rather than to animal parts.…”
Section: Discussioncontrasting
confidence: 99%
“…Such birefringency could make the unwary think of the possibility of the fragmented cuticle of a maggot. In fact, polarizable material has been presented in the literature as supportive for the diagnosis of cutaneous myiasis . Misdiagnosis can be avoided if one pays attention to the cuticle layers in the maggot (epi, exo and endo), which differ from the pericarp structures shown here.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Corneocytes of the stratum corneum are polarizable and Gonzalez‐Serva et al have reported polarizable crystals in sebum raising the possibility that the intraabdominal birefringent material in both scabies and Demodex scybala may be related to an intrinsic characteristic of the mites' diet. The polariscopic features of other parasitic organisms such as tungiasis or larva migrans have not been described, although the mouth hooks, larval spiracles and spines of the intradermal parasite, Dermatobia hominis , are reportedly polarizable . As the size and location of these parasites are very different than scabies, they are not typically considered in the same differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…When the larva is well conserved, a large central tubular cavity; the digestive tube; the respiratory tract, composed of smaller tubular structures; a circulatory system; and the pigmented posterior respiratory spiracle can all be identified (26, 56). Polarized light microscopy may show a bright retractile material (328).…”
Section: Cutaneous Myiasismentioning
confidence: 99%